Importance of food safety in the travel decisions of Singaporeans - Foo, Kenneth Woei Kuan (2008)
Food safety was found to be of secondary importance in the travel decisions of Singaporeans. Africa was the most avoided region due to food safety concerns. Friends and relatives, magazines and newspapers and tour agents were the most common sources of health and food safety information.